ANALISIS LINGKUNGAN DALAM PERUMUSAN STRATEGI PEMASARAN - Agung Yuniarinto; Albab, Tiriswati Ulil (Jurnal Kewirausahaan dan Inovasi, 2022)
Lulaya Shop is an online shop engaged in fashion business focusing on females. Business competition especially in fashion in Situbondo regency has urged the shop to create an accurate marketing strategy. The objective of this research is to identify the company’s internal and external factors and to obtain a marketing strategy that suits the business’ internal and external factors. The data of this qualitative descriptive research was obtained from interviews with the shop’s oner and two customers, as well as from observations and documentation. In this study, matrices of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Strength, Weakness, Opportunities, Threat (SWOT), Internal External (IE), and Quantitative Strategic Planning Matrix (QSPM) were used. Based on the analysis, the most appropriate strategy for  Lulaya shop is market penetration. The business can market their product through Shopee, can use Instagram more extensively, promote their products through Instagram Ads, improve their skill in design for better products and more attractive social media feeds, enhance the quality of their products, take partners to reach wider spectrum of customers, sell new products such as kids wears since their market are females who are also mostly mothers who also think about the children’s clothes, and hold discount and member card programs.